2018
DOI: 10.1002/mrm.27385
|View full text |Cite
|
Sign up to set email alerts
|

Determination of multipool contributions to endogenous amide proton transfer effects in global ischemia with high spectral resolution in vivo chemical exchange saturation transfer MRI

Abstract: Combined amide and amine effects dominated the MTR changes after global ischemia, indicating that MTR is predominantly pH-sensitive and suitable for detecting tissue acidosis following acute stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 50 publications
9
69
0
Order By: Relevance
“…Thus, the stronger correlation between T 1 -normalized MTR asym and AREX compared with T 1 -normalized MTR asym and MTR asym suggests that it is not necessary to correct for MT, but necessary to compensate for T 1 in cases of acute stroke. This finding was in agreement with previous studies that reported nearly no changes in MT, 45 but significant changes in T 1 in cases of acute stroke. 36,39 It is also worth noting that previous studies have found that APT effect does not linearly depend on T 1 .…”
Section: F I G U R Esupporting
confidence: 94%
“…Thus, the stronger correlation between T 1 -normalized MTR asym and AREX compared with T 1 -normalized MTR asym and MTR asym suggests that it is not necessary to correct for MT, but necessary to compensate for T 1 in cases of acute stroke. This finding was in agreement with previous studies that reported nearly no changes in MT, 45 but significant changes in T 1 in cases of acute stroke. 36,39 It is also worth noting that previous studies have found that APT effect does not linearly depend on T 1 .…”
Section: F I G U R Esupporting
confidence: 94%
“…Concerning the APTw signal of WMH, pH may play a decisive role. In ischemic lesions, the exchange rate of amide protons is affected due to its sensitivity by pH changes (21,22). In acute ischemic stroke, elevated APTw signal intensity values are attributed to intracellular acidosis (22,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In ischemic lesions, the exchange rate of amide protons is affected due to its sensitivity by pH changes (21,22). In acute ischemic stroke, elevated APTw signal intensity values are attributed to intracellular acidosis (22,(35)(36)(37)(38). This intracellular tissue acidification will alleviate in the follow up if clinical symptom improvement occurs after ischemic stroke (with or without treatment) (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTR asym is heterogeneous across the intact white and gray matter despite their little pH difference . It has been shown that in rats, the T 1w ‐normalized CEST effects for the intact brain WM and GM are 2.08 ± 0.20 vs. 2.00 ± 0.23%/s (APT), −1.79 ± 0.88 vs. −0.89 ± 0.97%/s (MT contrast asymmetry) and 4.42 ± 0.58 vs. 3.38 ± 0.42%/s (nuclear overhauser enhancement, NOE), respectively . Indeed, the noticeable NOE and MT contrast between brain WM and GM despite their little pH difference suggest that NOE and MT effects are not pH specific.…”
Section: Introductionmentioning
confidence: 99%